Modulation of mitochondrial dynamics in skeletal muscle during endurance training: early activation of fission and late induction of fusion protein expression - Hisashi Takakura; Hitomi Banba; Tatsuya Yamada; Rikuhide Koma; Tsubasa Shibaguchi; Yudai Nonaka; Kazumi Masuda (Journal of Physical Fitness and Sports Medicine)
The mitochondria are highly plastic organelles. Exercise training alters mitochondrial dynamics (mitochondrial fission and fusion) in skeletal muscles and improves overall mitochondrial function by altering mitochondrial morphology and forming new networks. However, changes in mitochondrial dynamics over time during exercise training have not previously been observed. In the present study, we examined the changes in mitochondrial fission and fusion protein expression in rats over four weeks of endurance swimming training. The expression of the GTPase protein dynamin-related protein 1 (Drp1), a mitochondrial fission protein, increased during the early phase of the training period. In contrast, the expression of optic atrophy type 1 (OPA1), a mitochondrial fusion protein, was increased in the late phase of the training period. These data suggest that mitochondrial fission was increased in the early phase, and mitochondrial fusion was initiated partially in the late phase, of the training period. In conclusion, mitochondrial dynamics may be modulated depending on the phase of muscular adaptation to exercise training. This modulation contributes to enhanced mitochondrial function in skeletal muscle.